Non-compete Agreements in a Rigid Labour Market: The Case of Italy - Tito Boeri; Andrea Garnero; Lorenzo Giovanni Luisetto (Institute of Labor Economics (IZA), 2023)
Non-compete clauses (NCCs) limiting the mobility of workers have been found to be rather widespread in the US, a flexible labour market with large turnover rates and a limited coverage of collective bargaining. This paper explores the presence of such arrangements in a rigid labour market, with strict employment protection regulations by OECD standards and where all employees are, at least on paper, subject to collective bargaining. Based on a representative survey of employees in the private sector, an exam of collective agreements and case law, we find that in Italy i) collective agreements play no role in regulating the use of NCCs while the law specifies only the formal requirements, ii) about 16% of private sector employees are currently bound by a NCC, iii) NCCs are relatively frequent among low educated employees in manual and elementary low paid occupations having no access to any type of confidential information, and iv) in addition to NCCs, a number of other arrangements limit the post-employment activity of workers. Many of the NCCs do not comply with the minimum requirements established by law and yet workers do not consider them as unenforceable and appear to behave as they were effective. Even when NCCs are unenforceable they appear to negatively affect wages when they are introduced without changing the tasks of the workers involved. Normative implications are discussed in the last section of the paper.
Keywords: J31; J41; J42; L40; 330; non-compete clauses; monopsony; labour market concentration